2015
DOI: 10.1111/ijlh.12386
|View full text |Cite
|
Sign up to set email alerts
|

Autovalidation rates in an outpatient coagulation laboratory

Abstract: We conclude that an integrated system can result in a high autovalidation rate in a high-volume outpatient coagulation laboratory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 10 publications
1
4
0
Order By: Relevance
“…Once the algorithm is technically set up, decision upon whether all tests or specific test panels will be subject to AV should be made. The results of the survey showed that AV is most commonly applied to routine biochemistry tests, haematology and coagulation tests, and similar results are reported in literature (2,(14)(15)(16)(17). Some studies reported the use of AV for special biochemistry tests, i.e.…”
Section: Discussionsupporting
confidence: 73%
“…Once the algorithm is technically set up, decision upon whether all tests or specific test panels will be subject to AV should be made. The results of the survey showed that AV is most commonly applied to routine biochemistry tests, haematology and coagulation tests, and similar results are reported in literature (2,(14)(15)(16)(17). Some studies reported the use of AV for special biochemistry tests, i.e.…”
Section: Discussionsupporting
confidence: 73%
“…Most of the published literature to date is limited to autoverification rules written in the hematology analyzer and the LIS. 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 Reported autoverification rates for CBC results have ranged from 63% when rules were built in the analyzer 10 to 81% when written in LIS. 12 Similarly in coagulation, reported autoverification rates have ranged from 65% to 82%.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 10 High rates of LIS-based autoverification were achieved in an outpatient hematology/coagulation laboratory; however, outpatient samples may be less complex to result than predominantly inpatient population. 6 , 7 We were able to find 1 report of a hematology laboratory that built autoverification rules in middleware and these authors used similar instrumentation and middleware as our laboratory. 13 They achieved an autoverification rate of 93.5% for CBC and 89.9% for individual CBC components, which was similar to our results of 97.2% for all CBCD and 88.3% for WBC differentials.…”
Section: Discussionmentioning
confidence: 99%
“…The AV system in this study was designed according to three different decision limits that have been recommended in the literature ( 6 , 13 , 20 ). The AV passing rate was found between 77% and 85% based on the algorithms we developed.…”
Section: Discussionmentioning
confidence: 99%
“…A higher percentage of test results (83%) was autoverified based on the reference range ± TEa criterion. Previous studies have shown that by using the reference range ± TEa criterion, the AV passing rate varies between 73% and 85% ( 8 , 20 ). A study conducted by Shih et al concluded that the rate of AV was 92% for 25,526 patient reports and 42 biochemical tests using the 2nd and 98th percentiles of cumulative patient data ( 21 ).…”
Section: Discussionmentioning
confidence: 99%